Development and Acceptability Test of Enteral Food Formulation Based on Local Foods “KarotenPe” Tempeh Flour and Carrot Flour High in BCAA for Cancer Disease - Mastura, Khantsa; Visi Asmara, ⁠An-nisa; Sarbini, ⁠Dwi (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Cancer can impair nutritional status due to alterations in the metabolism of energy, protein, fat, and micronutrients, which may lead to malnutrition and require nutritional support through enteral formulas. The development of enteral nutrition based on local food ingredients offers a potential alternative to improve accessibility and nutritional quality for patients. Objective: This study aimed to develop an enteral formula based on tempeh flour as a source of plant protein and carrot flour as a source of beta-carotene, and to evaluate its physical characteristics and sensory acceptability. Method: A completely randomized design with three formulations was employed, analyzing viscosity, osmolarity, flow rate, moisture content, color parameters, and sensory evaluation. Result and Discussion: All formulations met viscosity and flow rate standards. Formula 2 demonstrated the closest flow rate to the commercial product and achieved the highest sensory scores. However, osmolarity across all formulations exceeded recommended ranges, and moisture content surpassed the ideal limit, potentially affecting product stability. No significant differences were found among formulations in sensory parameters. Conclusions: Formula 2 was identified as the most preferred formulation with characteristics closest to the commercial product. However, improvements are required in terms of osmolarity and moisture content to meet the standard requirements for enteral nutrition products